2019
DOI: 10.3390/nu11071541
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Gut Microbiota Affecting Serum Level of Undercarboxylated Osteocalcin in Patients with Crohn’s Disease

Abstract: Several reports have indicated a possible link between decreasing plasma levels of vitamin K and bone mineral density. It has been suggested that intestinal bacteria contribute to maintenance of vitamin K. Several factors are involved in the reduction of vitamin K in patients with Crohn’s disease (CD). We aimed to assess the relationship between gut microbiota and alternative indicators of vitamin K deficiency in patients with CD. We collected the feces of 26 patients with clinically inactive CD. We extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…In addition, osteocalcin has a role in bone remodelling based on its found that the diversity of the gut microbiota affects the serum level of osteocalcin in patients [69]. This means that the occurrence of osteoporosis causes uneven cartilage stress, which further aggravates joint and cartilage damage, increasing the severity of knee osteoarthritis [57].…”
Section: Effect Of Gut Microbiota Dysbiosis On Oa Network Correlationmentioning
confidence: 99%
“…In addition, osteocalcin has a role in bone remodelling based on its found that the diversity of the gut microbiota affects the serum level of osteocalcin in patients [69]. This means that the occurrence of osteoporosis causes uneven cartilage stress, which further aggravates joint and cartilage damage, increasing the severity of knee osteoarthritis [57].…”
Section: Effect Of Gut Microbiota Dysbiosis On Oa Network Correlationmentioning
confidence: 99%
“…The role of osteocalcin in bone remodeling, speci c expression and regulation in osteoblasts which is important biomarker in osteoporosis and level of reduced Osteocalcin expression were maintained in human osteoarthritic chondrocytes and represented a suitable biomarker of osteoarthritic chondrocyte activation [63]. Wagatsuma et.al found that diversity of gut microbiota affecting serum level of osteocalcin in patient [64]. It is means that the occurrence of osteoporosis causes uneven cartilage stress, which further aggravates joints and cartilage damage which make knee osteoarthritis more serious [57].At the same time, the exacerbation of osteoarthritis reduces the activity of mice and reduces stress stimuli which further aggravated osteoporosis [58].…”
Section: Discussionmentioning
confidence: 99%
“…The present Special Issue on “Targeted Nutrition in Chronic Disease” includes three reviews [ 2 , 3 , 4 ] and seven original research articles [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. A meta-analysis on coffee intake and obesity suggested that higher coffee intake was associated with modestly lower body mass index (BMI) and waist circumference in men but not in women [ 2 ].…”
mentioning
confidence: 99%
“…Likewise, it has been suggested that vitamin K is involved in bone mineral density and chronic disease development. The bacterial flora in the gut may contribute to the maintenance of vitamin K, and in this Special Issue, Wagatsuma et al demonstrated that vitamin K deficiency in patients with clinically inactive Crohn’s disease reduced the diversity of the gut microbiota [ 7 ]. The authors concluded that the composition of the gut microbiota was similar to that in patients with active Crohn’s disease [ 7 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation